C/EBPβ Isoforms Expression in the Rat Brain during the Estrous Cycle - Valeria Hansberg-Pastor; Ana Gabriela Piña-Medina; Aliesha González-Arenas; Ignacio Camacho-Arroyo (International Journal of Endocrinology)
The CCAAT/enhancer-binding protein beta (C/EBPβ) is a transcription factor expressed in different areas of the brain that regulates the expression of several genes involved in cell differentiation and proliferation. This protein has three isoforms (LAP1, LAP2, and LIP) with different transcription activation potential. The role of female sex hormones in the expression pattern of C/EBPβ isoforms in the rat brain has not yet been described. In this study we demonstrate by western blot that the expression of the three C/EBPβ isoforms changes in different brain areas during the estrous cycle. In the cerebellum, LAP2 content diminished on diestrus and proestrus and LIP content diminished on proestrus and estrus days. In the prefrontal cortex, LIP content was higher on proestrus and estrus days. In the hippocampus, LAP isoforms presented a switch on diestrus day, since LAP1 content was the highest while that of LAP2 was the lowest. The LAP2 isoform was the most abundant one in all the three brain areas. The LAP/LIP ratio changed throughout the cycle and was tissue specific. These results suggest that C/EBPβ isoforms expression changes in a tissue-specific manner in the rat brain due to the changes in sex steroid hormone levels presented during the estrous cycle.